2025
DOI: 10.1039/d4ew00225c
|View full text |Cite
|
Sign up to set email alerts
|

Solid–liquid partitioning of dengue, West Nile, Zika, hepatitis A, influenza A, and SARS-CoV-2 viruses in wastewater from across the USA

Laura Roldan-Hernandez,
Camila Van Oost,
Alexandria B. Boehm

Abstract: Limited information is available on the fate of respiratory and arthropod-borne viruses in wastewater. Enteric viruses have been extensively studied in wastewater treatment plants, however partition coefficients have not been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
4
3
Order By: Relevance
“…We observed the highest K d for measles of 219.1 ± 99.3 mL/g, as compared to 57.5 ± 38.6 mL/g for mumps and 3.4 ± 2.5 mL/g for rubella. These K d results are lower than those determined in previous studies for other enveloped RNA viruses, such as SARS-CoV-2, influenza A, RSV, and Zika, in wastewater 55 , 56 . One possible reason is that using the PCR inhibitor removal kit minimized the inhibition during the partitioning experiment of Roldan-Hernandez et al (2023, 2024) 55 , 56 , while significant inhibitory effects were observed in the solids sample extracts in our study.…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…We observed the highest K d for measles of 219.1 ± 99.3 mL/g, as compared to 57.5 ± 38.6 mL/g for mumps and 3.4 ± 2.5 mL/g for rubella. These K d results are lower than those determined in previous studies for other enveloped RNA viruses, such as SARS-CoV-2, influenza A, RSV, and Zika, in wastewater 55 , 56 . One possible reason is that using the PCR inhibitor removal kit minimized the inhibition during the partitioning experiment of Roldan-Hernandez et al (2023, 2024) 55 , 56 , while significant inhibitory effects were observed in the solids sample extracts in our study.…”
Section: Resultscontrasting
confidence: 74%
“…These K d results are lower than those determined in previous studies for other enveloped RNA viruses, such as SARS-CoV-2, influenza A, RSV, and Zika, in wastewater 55 , 56 . One possible reason is that using the PCR inhibitor removal kit minimized the inhibition during the partitioning experiment of Roldan-Hernandez et al (2023, 2024) 55 , 56 , while significant inhibitory effects were observed in the solids sample extracts in our study. In addition, partition coefficients and recovery rates vary across different viruses, and also due to numerous other factors, such as the wastewater matrix, liquid-solid separation methods, and wastewater processing methods 16,5558 .…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…During the time between sample collection and transport (0–3 days), we expect minimal losses of the RNA target based on results of IAV RNA persistence studies . Upon receipt of the laboratory, samples are processed immediately to measure IAV M gene and PMMoV gene concentrations in the solid fraction of wastewater; the solid fraction was chosen for measurements as work indicates that these targets are enriched orders of magnitude in solids compared to liquids in wastewater , Since the methods are described in detail elsewhere, , they are not provided in the main text and are summarized in the SI. PMMoV is an endogenous plant virus present in wastewater and serves as an internal process control.…”
Section: Methodsmentioning
confidence: 99%